7 Nutrition and global challenges: resilient food systems for healthy and sustainable diets. (12th April 2022) - Hachem, Fatima; Mahy, Lina; Ray, Sumantra; Kumar, Vijay; Johnsen, Jorgen; Raman, Kanan
Abstract : Can diets be healthy and sustainable? This was the question posed by Dr Hachem from the Food and Agriculture Organization (FAO) at the NNEdPro Sixth International Summit on Nutrition and Health. The market value of the global food system is an estimated 10 trillion, while the hidden costs of global food and land use systems sum up to an astounding 12 trillion, according to the Food and Land Use Coalition 2019 report and highlighted by Lina Mahy, from the World Health Organization (WHO). Of those hidden costs, more than half is attributed to unhealthy diets and harmful farming practices. Food systems must enhance food security and nutrition for all, be inclusive, and have a positive impact on the health of people and planet, as well as be economically viable, in line with Nutrition Decade Action Area 1, Sustainable, resilient food systems for healthy diets. There are 16 guiding principles to achieve healthy diets sustainably produced, with eight related to nutrition, including promotion of exclusive breastfeeding, variety and balance across food groups, consumption of whole grains, legumes, nuts and fruits and vegetables and moderate to small amounts of animal source foods. Governments can signal commitment to a more sustainable and healthy future through the development and dissemination of food-based dietary guidelines that embed health and sustainability objectives. Professor Ray of the NNEdPro Global Centre, spoke on the role of global knowledge networks in response to global nutrition challenges, using the example of the Mobile Teaching Kitchens (MTK) model. The MTK project uses a scalable, micro-level innovation model for health and social innovation in partnership with marginalised populations. The model aims to improve the nutrition knowledge and capacity of the population through demonstration by Teaching Kitchen champions, who are trained nutrition educators. Qualified dietitians and nutritionists share knowledge and skills with community-based volunteers, to support the development of Teaching Kitchen champions in a 'See One, Do One, Teach One' model. Promotion of nutritious, affordable, culturally appropriate, and environmentally sustainable food is central to the MTK model. Investing in some of the most marginalised in society can have an upward social and health impact including localised supply chains and microenterprise and aligns with the Sustainable Development Goals and the UN Decade of Action on Nutrition (2016-2025). Professor Kumar, of the Zero Budget Natural Farming Programme of Rythu Sadhikara Samstha, continued the discussion on diet sustainability, focusing on the role of climate resilient, community managed natural farming related to nutrition and food security. To set the scene, it was discussed that the food system is facing multiple crises which pose serious threats to food security, nutrition, and the livelihood of farmers. The environmental crisis places additional strain on the food system, including soil degradation and continuous loss of soil organic matter, water stress, global warming, water and air pollution, and decreased biodiversity, thus increasing the number of people at risk of food insecurity and poor nutrition, and worsening farmer distress. While some agricultural practices are historical, namely, deforestation, forest fires, ploughing and keeping lands fallow, recent use of chemical fertilizers and pesticides (biocides) have accelerated environmental decline. Regenerative agriculture, such as zero budget natural farming, was posed an alternative. It is defined as a holistic land management practice that leverages the power of photosynthesis in plants to close the carbon cycle, and build soil health, crop resilience and nutrient density. Professor Kumar reiterated the value of local knowledge networks, namely, organised women in natural farming and champion farmers, as a strength in scaling up nutrition interventions such as this. Collective action and peer learning can support behaviour change and address inequities. Collective efforts are key to sustained impact and in the words of Professor Kumar, 'If you want to change a farmer, you have to change an entire village' .